INFLUENCE OF GAS THERMAL PROCESS PARAMETERS SPRAYING OF COATINGS FOR THEIR WEAR RESISTANCE AND ADHESION STRENGTH - Lopata, Oleksandr (Problems of Friction and Wear, 2023)
On principle of equivalent tensions of adhesive connection, the estimation of remaining tensions is conducted in coverage. For this purpose, graphic differentiation of experimental dependence of adhesive durability is utilized from the thickness of coverage. Functional connection is set between adhesive durability, thickness of coverage, critical deformation of basis and remaining tensions. It allows choosing the parameter When using electrical contact treatment after gas-thermal spraying of coatings, positive results were obtained: the value of residual stresses does not exceed 200 MPa; parts with gas-thermal coatings that have undergone electrocontact treatment are characterized by a smooth change in hardness from the coating to the surface of the part and an increased diffusion zones of the system «basis-coverage» at finish treatment and exploitation. the amount of pressure and the technological scheme of the electrical contact treatment process significantly affect the level of residual stresses and the adhesion strength of the coatings. From this point of view, preference should be given to the application of coatings by gas-thermal spraying with subsequent electrical contact treatment with a gradual increase in temperature and pressure of the process. The method of graphic differentiation of the experimental dependence of the adhesive strength on the thickness of the coating was used to determine the residual stresses in the coatings obtained by gas-thermal spraying with subsequent electrical contact treatment. According to the principle of equivalence of residual stresses and critical deformation of the part during peeling of the coating, a functional relationship of adhesive strength, thickness of the coating, critical deformation of the part and residual stresses was established. This dependence allows you to determine the characteristics of coated parts for their operating conditions.